2013
DOI: 10.1089/dia.2013.0147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glycemic Control on Heart Rate Variability in Youth with Type 1 Diabetes: The SEARCH CVD Study

Abstract: Aim: This study explored the role of glycemic control on cardiac autonomic function, measured by heart rate variability (HRV), in youth with type 1 diabetes. Patients and Methods: A retrospective cohort of 345 youth with type 1 diabetes (mean age, 18.5 years; duration, 10 years) participating in the SEARCH for Diabetes in Youth study were enrolled in the ancillary SEARCH Cardiovascular Disease (CVD) study. Anthropometric, metabolic, and HRV parameters were collected at the current research visit. Glycemic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
4
18
0
1
Order By: Relevance
“…This pattern of autonomic dysfunction is consistent with enhanced sympathetic tone relative to parasympathetic or vagal tone, as has been also observed in T1D populations using spectral analysis of resting electrocardiograms …”
Section: Discussionsupporting
confidence: 86%
“…This pattern of autonomic dysfunction is consistent with enhanced sympathetic tone relative to parasympathetic or vagal tone, as has been also observed in T1D populations using spectral analysis of resting electrocardiograms …”
Section: Discussionsupporting
confidence: 86%
“…Therefore, our results may support a positive relationship between the original diabetes‐related chronic stress and a dysfunctional ANS response to acute stress. Observation of ANS dysfunction in T1D has already been reported . Similarly, the larger amplitude of HF changes in the context of acute stress has also been observed in people with other chronic stress conditions ().…”
Section: Discussionsupporting
confidence: 52%
“…Recent studies have supported the theory that hyperglycemia also impairs neuronal regeneration, and suggested that an increase in plasma superoxide generation may be able to predict decline in cardiac nerve function, and in particular may be the main determinant in early cardiac autonomic dysfunction 4850. In relation to CAN, increased ROS is thought to depress autonomic ganglion synaptic transmission, contributing to increased risk of fatal cardiac arrhythmias, as well as to sudden death after myocardial infarction due to posttranslational protein modifications 51…”
Section: Pathogenesis Of Canmentioning
confidence: 97%